Is The Nurse Still Needed In Anesthesia? - White, Ian (Operating Room Nurses Association of Canada Journal, 1994)
The health care industry is experiencing extremely unsettled times and all health care professionals are profoundly affected. Health care is responsible for approximately 33% of most provincial budgets and expenditures and represents approximately 9.6% of the Gross Domestic Product (GDP). Health care costs have continued to increase two to four percent above the increase in GDP despite the “cut backs” instituted by governments over the past several years. If governments are to reduce the deficit, without increasing revenues from taxes, they are obliged to reduce overall expenditures and health care, then, will be a prime target.